PERILAKU NON-VOTING DALAM PEMILIHAN KEPALA DAERAH KOTA PADANG PERIODE 2008-2013 (Studi Kasus di Kecamatan Koto Tangah) - Aina, Aina (Humanus, 2013)
The direct provincial and mayoral election often witnesses the tendency of low voter turnout, as happened in Padang city mayoral election in 2008. This research seeks to reveal the non-voting behavior and the causes of the behavior in Koto Tangah district, which has the lowest voter turnout; 42.51%. This research is a descriptive-qualitative where data is obtained by using in-depth interview technique and documentation study. Snowball sampling is used to select sample of voters who vote in Padang 2008 election. The data was then analyzed using qualitative method. The result shows that there were two types of non-voting behavior in Koto Tangah community in Padang 2008 mayoral election; (1) did not come to the ballot box; (2) did come to the ballot box but did not cast ballots properly. The behavior was caused by several factors; (1) psychological factor; (2) factor of political system; (3) factor of political trust; and (4) factor of socio-economic status. Psychological factor means non-voters’ characters tend to be apathetic and ignorant of politics. In terms of political system factor, non-voting behavior was driven by dissatisfaction with the government’s performance which showed no change. Political trust factor showed that most non-voters do not believe in the processes and results of the local elections. Meanwhile, in socio-economic status, most non-voters are educated. On the other hand, employment and income also contributed to the non-voting behavior. Key words: direct local election, Padang mayoral election, low voter turnout, non-voting behavior